United Nations-Led Ceasefire Enforcement in the Israel-Palestine Conflict: Analyzing Challenges, Successes, and the Path Forward - Hossan, Md. Alomgir; Md. Shakirul Islam (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This research examines the challenges and successes of United Nations (UN)-led ceasefire enforcement in the protracted Israel-Palestine conflict. It explores the operational, political, and diplomatic complexities the UN faces in mediating and maintaining ceasefires in one of the world's most contentious and enduring conflicts. The study highlights the limitations of UN peacekeeping mechanisms, such as impartiality and resource constraints, and the influence of powerful state actors with vested interests in the region. Through a review of historical ceasefires and their enforcement, the research identifies key factors contributing to both their failures and occasional successes, such as localized trust-building efforts, international diplomatic pressure, and grassroots cooperation. It underscores the need for more robust frameworks that address asymmetries of power, incorporate regional stakeholders, and enhance the UN’s capacity for long-term conflict resolution. The findings offer insights into the broader implications for international peacekeeping and propose recommendations for strengthening the UN's role in navigating complex geopolitical disputes like Israel-Palestine.